An analysis of food and beverage advertising on bus shelters in a deprived area of Northern England. Issue 7 (3rd July 2022) - Finlay, Amy Heather; Lloyd, Scott; Lake, Amelia; Armstrong, Thomas; Fishpool, Mark; Green, Mark; Moore, Helen J; O'Malley, Claire; Boyland, Emma J
Abstract: Objective: To quantify the extent of food and beverage advertising on bus shelters in a deprived area of the UK, to identify the healthfulness of advertised products, and any differences by level of deprivation. The study also sought to assess the creative strategies used and extent of appeal to young people. Design: Images of bus shelter advertisements were collected via in person photography (in 2019) and Google Street View (photos recorded in 2018). Food and beverage advertisements were grouped into one of seventeen food categories and classified as healthy/less healthy using the UK Nutrient Profile Model. The deprivation level of the advertisement location was identified using the UK Index of Multiple Deprivation. Setting: Middlesbrough and Redcar and Cleveland in South Teesside. Participants: N/A Results: Eight hundred and thirty-two advertisements were identified, almost half (48·9 %) of which were for foods or beverages. Of food and non-alcoholic beverage adverts, 35·1 % were less healthy. Most food advertisements (98·9 %) used at least one of the persuasive creative strategies. Food advertisements were found to be of appeal to children under 18 years of age (71·9 %). No differences in healthiness of advertised foods were found by level of deprivation. Conclusions: Food advertising is extensive on bus shelters in parts of the UK, and a substantial proportion of this advertising is classified as less healthy and would not be permitted to be advertised around television programming for children. Bus shelter advertising should be considered part of the UK policy deliberations around restricting less healthy food marketing exposure.